Early left‐right asymmetries during axial morphogenesis in the chick embryo. Issue 6 (5th April 2014) - Otto, Annalena; Pieper, Tobias; Viebahn, Christoph; Tsikolia, Nikoloz
Summary: The primitive node is the "hub" of early left‐right patterning in the chick embryo: (1) it undergoes asymmetrical morphogenesis immediately after its appearance at Stage 4; (2) it is closely linked to the emerging asymmetrical expression of nodal and shh at Stage 5; and (3) its asymmetry is spatiotemporally related to the emerging notochord, the midline barrier maintaining molecular left‐right patterning from Stage 6 onward. Here, we study the correlation of node asymmetry to notochord marker expression using high‐resolution histology, and we test pharmacological inhibition of shh signaling using cyclopamine at Stages 4 and 5. Just as noggin expression mirrors an intriguing structural continuity between the right node shoulder and the notochord, shh expression in the left node shoulder confirms a similar continuity with the future floor plate. Shh inhibition at Stage 4 or 5 suppressed nodal in both its paraxial or lateral plate mesoderm domains, respectively, and resulted in randomized heart looping. Thus, the "primordial" paraxial nodal asymmetry at Stage 4/5 (1) appears to be dependent on, but not instructed by, shh signaling and (2) may be fixed by asymmetrical roots of the notochord and the floor plate, thereby adding further twists to the node's pivotal role during left‐right patterning. genesis 52:614–625, 2014. © 2014 Wiley Periodicals, Inc.